Environmental sustainability: what Islam propagates - Jusoff, Kamaruzaman; Abu Samah, Siti Akmar (IDOSI Publications, 2011)
Through the teaching of Islam, the earth is mentioned more than four hundred times in the Qur’an, whereas the sky and beyond are mentioned only about three hundred times. This article intends to explore and share that Islam does understand the earth to be subservient to humankind. Therefore, the earth should not be administered and exploited irresponsibly. Based on the teachings and principles of Islam, one leads to a strong sense of goodness and purity of the earth. In Islam, human and environment interaction is guided by the notion of the person as a vicegerent or steward of the earth. The extensive evidence provided by the Holy Quran is indicative that the earth is an important protected element for future sustenance of the next generation and is to be a safe place to keep. Despite that, the concept of sustainable development on the earth is complex and murky. It lends itself to several interpretations and it is still in the process of evolution. However, an evaluation of different approaches to the concept leads to the same goal. The underlying issue behind the various interpretations is eventually the concern on how the environmental perimeter is sustained. The rapid deterioration of human environment is nothing but a crisis of values. Muslims and mankind at large are being instructed to look after the environment and not to damage it. Therefore, an Islamic way of a sustainable environmental life entails living in “peace and harmony (salam)" at individual, social as well as ecological levels. All human activities have some impact on the environment. And for that this paper will display the reconciliation of Islam and environmental sustainability through the perennial reference of the Holy Quran and the Words of Prophet Muhammad (pbuh).